Colistin Resistance of Pseudomonas aeruginosa Isolated from Snakes in Taiwan - Po-Yu Liu; Ling-Ling Weng; Shu-Ying Tseng; Chou-Chen Huang; Ching-Chang Cheng; Yan-Chiao Mao; Kwong-Chung Tung (Canadian Journal of Infectious Diseases and Medical Microbiology)
This study included fifty-eight isolates of P. aeruginosa from the oral cavity of snakes that were recruited from clinical cases, captive and wild snakes. The minimum inhibitory concentrations (MICs) for the determination of susceptibility were identified by the broth microdilution method. Polymerase chain reaction (PCR) was employed to detect β-lactamases genes. With regard to antipseudomonal antibiotics, the lowest nonsusceptible rates were in aztreonam (15%), piperacillin/tazobactam (12%), and amikacin (9%). The nonsusceptible rates were high in gentamicin (33%) and colistin (55%). Meanwhile, blaTEM presented in 100% of isolates where blaAmpC, blaOXA-1, and blaOXA-10 came at 94.8%, 89.7%, and 27.6%, respectively. Emergence of multidrug resistant (MDR) strains and colistin-resistant strains highlights the potential breach of public health as P. aeruginosa could be transmitted through either direct contact or indirect dissemination through the environment. This study reports that the highly resistant P. aeruginosa from snakes’ oral cavity were discovered for the very first time in Taiwan.